Unsafe Action Of Gadget And Eye Fatigue in Jambi University Psychology Students - Guspianto; Rd. Halim; Ummi Kalsum; Budi Aswin; Meisya Dwi Anggi Marta Anggi (Saintika Medika : Jurnal Ilmu Kesehatan dan Kedokteran Keluarga, 2024)
In the 4.0 Revolution Era, technology is becoming increasingly advanced, impacting eye fatigue. This study aimed to analyze the relationship between unsafe actions of gadget use and subjective complaints of eye fatigue among Psychology students at Jambi University in 2023. This was a cross-sectional study with a sample of 106 students using stratified random sampling. The research was conducted from March 2023 to February 2024 at the Psychology Study Program, Jambi University. Univariate and bivariate analyses were performed using the Chi-square test with 95% confidence level. The dependent variable was subjective complaints of eye fatigue measured by the DES-Q, while the independent variables were glasses use, viewing duration, viewing distance, and gadget use position. 60.4% had subjective eye fatigue complaints. Variables associated with subjective eye fatigue complaints were long gadget viewing duration (PR: 1.945 (95%CI; 0.936-4.042)) and short smartphone viewing distance (PR: 1.532 (95%CI; 1.092-2.151)). No association was found for glasses use (PR: 0.986 (95%CI; 0.657-1.479)), laptop viewing distance (PR: 0.892 (95%CI; 0.649-1.227)), and gadget use position (PR: 1.027 (95%CI; 0.697-1.514)). Conclusion: Long gadget viewing duration >4 hours and short smartphone viewing distance <30 cm were risk factors for subjective eye fatigue complaints. Students are advised to take eye breaks every 2 hours.